Silver-coated nickel paste and preparation method thereof, and metallization method of high-temperature sintered crystalline silicon solar cell
By adopting specific silver-clad nickel powder and surface-modified silver-clad nickel paste, the problem of difficulty in controlling free nickel during high-temperature sintering is solved, efficient metallization is achieved, line resistance and cost are reduced, and high photoelectric conversion efficiency is maintained.
Patent Information
- Application Number
- CN202510149201.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-11
AI Technical Summary
In the prior art, free nickel generated by silver-clad nickel paste during high temperature sintering is difficult to control, resulting in the formation of nickel oxide, improving line resistance, and limiting the improvement of the conversion efficiency of solar cells.
A specific silver-clad nickel powder is used, with a resistivity of ≤96μΩ·cm, an oxidation resistance of ≤205μΩ·cm, and a titrated nickel content of ≤0.01mol/L. Through surface modification treatment, combined with appropriate formulas and processes, a high-reliability silver-clad nickel paste is prepared for metallization of high-temperature sintered crystalline silicon solar cells.
The efficient metallization of silver-clad nickel paste during high-temperature sintering is achieved, which reduces the line resistance and maintains the contact resistance. The adjusted photoelectric conversion efficiency is 0% to 2% lower than that of pure silver paste, and effectively reduces the cost.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive pastes, and in particular relates to silver-coated nickel paste and a preparation method thereof, and a high-temperature sintered crystalline silicon solar cell metallization method. Background Art
[0002] At present, the metallization of crystalline silicon solar cells mainly adopts the process steps of screen printing of silver paste, drying, and high-temperature sintering. Due to the high silver content in the paste, the metallization process cost of crystalline silicon solar cells is relatively high.
[0003] In order to reduce the silver content in the slurry, silver-coated nickel powder is used to partially replace silver powder to make slurry in the related art. CN118367063A discloses a TOPcon solar cell metallization method and solar cell using silver-coated nickel slurry, wherein the silver-coated nickel conductive slurry used comprises 25-95% silver-coated nickel powder, 0-70% silver powder, 1-6% glass powder, 0.1-3% organic resin, 0.1-1% dispersant, 0-5% nickel diffusion regulator and solvent remainder. This slurry will produce free nickel during the metallization process, and nickel is easily oxidized to nickel oxide during the metallization process of high-temperature sintering of TOPcon solar cells, which increases the line resistance of TOPcon solar cells, thereby limiting the improvement of TOPcon solar cell conversion efficiency. During the metallization process, it is necessary to rely on nickel diffusion regulators and secondary laser sintering to form a nano-nickel tunneling layer, prevent the formation of large-sized nickel metal particles and nickel "dead layer" to affect the photoelectric conversion efficiency of the cell.
[0004] However, the amount of free nickel generated during the metallization process is not controllable, and the effect of the nickel diffusion regulator cannot guarantee that the negative effects of free nickel can be completely blocked / eliminated. Summary of the invention
[0005] The purpose of the present invention is to provide a silver-coated nickel paste and a preparation method thereof, and a high-temperature sintered crystalline silicon solar cell metallization method.
[0006] In the present invention, unless otherwise specified, "anti-oxidation resistivity" refers to the resistivity of the powder after calcination at 180°C for 10 minutes; "titration nickel content" is tested according to the method described in CN118961994A. The lower the titration nickel content, the better the density of the silver coating layer. The specific test steps are as follows: (1) Accurately weigh 2.00 g (error ≤ 0.001 g) of silver-coated nickel powder and add it to a clean 50 mL centrifuge tube; (2) Add 30 g of 3% by mass dilute sulfuric acid solution and 800 μL of 20% by mass hydrogen peroxide solution to the above centrifuge tube, cover the tube, and place it on an oscillator for vibration and mixing to obtain a mixed solution; wherein the oscillator frequency is 300 r / min and the oscillation time is 5 min; (3) After the shaking is completed, quickly take out the centrifuge tube and place it on the centrifuge for centrifugation (pay attention to the balance), and the centrifugal speed reaches 6000 rpm. The above process needs to be completed quickly. After centrifugation, take the supernatant in the centrifuge tube and put it into a new centrifuge tube for standby use; (4) Use a pipette to accurately measure 20 mL of the supernatant of the mixed solution and add it to a 250 mL conical flask, and add 50 mL of deionized water to the conical flask and shake it evenly; use a dispenser to add 19 mL of ammonium chloride buffer and 0.01 g of murexide indicator to the conical flask, shake it evenly, and the solution turns bright yellow to obtain a test solution; (5) Pour a 0.05 mol / L disodium ethylenediaminetetraacetic acid standard solution into a burette to a scale of 10 mL, and titrate the test solution at a low speed with the 0.05 mol / L disodium ethylenediaminetetraacetic acid standard solution until the test solution turns purple. The titration endpoint is reached if the solution does not return to its original color after shaking for 30 s. Record the volume of the 0.05 mol / L disodium ethylenediaminetetraacetic acid standard solution consumed in the titration. (6) Calculation of titration results: Calculation formula c = V1*C1 / V. Where, c: free nickel content, unit: mol / L; C1: concentration of disodium EDTA standard solution, unit: mol / L; V1: volume of disodium EDTA standard solution consumed in titration, unit: mL; V: volume of the supernatant of the mixed solution removed, unit: mL.
[0007] In a first aspect, the present invention provides a silver-coated nickel paste, which adopts the following technical solution: A silver-coated nickel paste is prepared from the following raw materials in percentage by weight: Conductive powder 80-95%, Glass powder 1-6%, Organic resin 0.1-3%, Thixotropic agent 0.5-0.8%, Other additives 0-1%, Solvent residue; The conductive powder is a mixture of silver-coated nickel powder and silver powder in a weight ratio of 1:(0-50); the resistivity of the silver-coated nickel powder used is ≤96μΩ·cm, the anti-oxidation resistivity is ≤205μΩ·cm, and the titrated nickel content is ≤0.01mol / L.
[0008] Furthermore, the silver content of the silver-coated nickel powder is 5wt%-50wt%.
[0009] Furthermore, the silver content of the silver-coated nickel powder is 5wt%-25wt%.
[0010] Furthermore, the silver-coated nickel powder is subjected to surface modification treatment, the specific steps of which are: The surface modifier of 5 / 10,000 to 5 / 1000 of the mass of the silver-coated nickel powder is evenly mixed with the silver-coated nickel powder to obtain the surface-modified silver-coated nickel powder.
[0011] Furthermore, the surface modifier is selected from one or more of terpineol, fatty acid, and dodecylbenzene sulfonic acid.
[0012] Furthermore, the particle size of the glass powder is 2-5 μm.
[0013] Furthermore, the glass powder is obtained by melting, cooling and ball milling mixed raw materials; the mixed raw materials are composed of the following components by weight percentage: Lead oxide (PbO) 35.3%-46.31%, Silicon oxide (SiO2) 5.38%-13.2%, Lithium oxide (Li2O) 2.64%-4.16%, Zinc oxide (ZnO) 1.85%-3.5%, Sodium oxide (Na2O) 1.22%-1.76%, Magnesium oxide (MgO) 0.43%-2.61%, Calcium oxide (CaO) 0.35%-1.57%, Tellurium oxide (TeO2) 0-30.53%, Barium oxide (BaO) 0-21.72%, Boron oxide (B2O3) 0-19.55%, Tungsten oxide (WO3) 0-9.65%, Copper oxide (CuO) 0-0.53%.
[0014] Furthermore, the specific preparation steps of the glass powder are: weighing raw materials according to a proportion, mixing to obtain a mixture; melting the mixture at 1250-1300° C. for 1.5 hours, quenching to obtain glass fragments; grinding and sieving the glass fragments to obtain glass powder; Furthermore, in the process of preparing glass powder, broken glass pieces are placed in a 20L vertical ball mill, 15kg of zirconia balls with a diameter of 5-10mm are added, 2kg of deionized water and oleic acid are added, and the mixture is stirred at a speed of 250r / min and ball-milled for 8h to obtain glass slurry; the glass slurry is sieved and dried to obtain glass powder with a particle size of 2-5μm.
[0015] Furthermore, the organic resin is a mixture of one or more of PVB resin, rosin resin, acrylic resin, phenoxy resin and ethyl cellulose.
[0016] Furthermore, the thixotropic agent is a mixture of one or more of polyamide wax, hydrogenated castor oil and polyethylene glycol.
[0017] Furthermore, the other auxiliary agent is a mixture of one or more of palmitic acid, silane coupling agent, dimethyl silicone oil, oleic acid, and TDO dispersant.
[0018] Furthermore, the solvent is selected from one or more of tripropylene glycol butyl ether, dibutyl phthalate, terpineol, tributyl citrate, butyl carbitol, triethylene glycol butyl ether, diethylene glycol butyl ether and benzyl alcohol.
[0019] In a second aspect, the present invention provides a method for preparing a silver-coated nickel slurry, which adopts the following technical scheme: The method for preparing the silver-coated nickel slurry described in any of the above items comprises weighing the raw materials according to the ratio, preliminarily mixing them with a homogenizer, and rolling them with a three-roller mill to obtain the silver-coated nickel slurry.
[0020] In a third aspect, the present invention provides a high temperature sintering crystalline silicon solar cell metallization method, which adopts the following technical solution: A high-temperature fired crystalline silicon solar cell metallization method is mainly applicable to high-temperature fired crystalline silicon solar cells such as PERC, TOPcon, and BC, and uses the silver-coated nickel paste described in any of the above items. The specific steps are: screen printing the silver-coated nickel paste on the surface of the high-temperature fired crystalline silicon solar cell, drying, and sintering in the air at 500-750°C to complete the metallization of the high-temperature fired crystalline silicon solar cell.
[0021] The present invention has the following beneficial effects: The silver-coated nickel conductive paste provided by the present invention contains densely coated high-reliability silver-coated nickel powder and does not contain a nickel diffusant. When printing a high-temperature fired crystalline silicon solar cell on the single back side, compared with pure silver paste, the line resistance is slightly higher, the contact resistance is basically the same, and the printed wet weight is basically the same. After adjustment, the photoelectric conversion efficiency is 0% to 2% lower than that of pure silver paste, and can be used to replace the silver paste of high-temperature fired crystalline silicon solar cells of pure silver powder; When the silver-coated nickel conductive paste of the present invention is used in a high-temperature sintering crystalline silicon solar cell metallization method, expensive silver is replaced by metal nickel, and the conductive paste effectively reduces costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the silver-coated nickel powder prepared in the preparation example; Figure 2A , Figure 2B This is a SEM image of the cross-section of the silver-coated nickel electrode after printing and sintering in Example 2. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the present application will be described in further detail below.
[0024] Preparation Example [Preparation of silver-coated nickel powder] The preparation steps of silver-coated nickel powder are: S1 Nickel powder surface pretreatment: Add 500g of micron-grade nickel powder and 2.5kg of deionized water into a beaker, stir to mix and form a suspension, then add 200g of sodium bicarbonate while stirring and put the beaker into an ultrasonic tank to ultrasonically clean the nickel powder, then settle and pour off the supernatant to obtain clean nickel powder, then add 5kg of deionized water and 200g of sodium hydroxide, and stir to obtain an activated nickel powder suspension.
[0025] S2 nickel powder dispersion: after step S1 is completed, the supernatant is poured off after sedimentation to obtain activated nickel powder, 10 kg of deionized water and 200 g of polyethylene glycol 200 are added to the activated nickel powder, and stirred evenly to form a nickel powder suspension to be silver-plated; Preparation of S3 silver plating solution: weigh 340g of silver nitrate and dissolve it in 1kg of deionized water, and add 300mL of concentrated ammonia water to form a complex silver plating solution.
[0026] S4 silver coating process: add the prepared silver plating solution to the nickel powder suspension obtained in step S2 at a rate of 20 mL / min, keep stirring, continue stirring and reacting for 30 minutes after the addition is completed to chemically plate silver on the surface of the nickel powder, and then add 300g of potassium sodium tartrate to promote the complete reduction and deposition of silver ions on the surface of the nickel powder, continue stirring and reacting for 30 minutes to end the coating process.
[0027] S5 cleaning and drying: After step S4, the plating solution is settled and the supernatant is poured out to obtain silver-coated nickel powder. 2 kg of deionized water is used each time to perform stirring cleaning-centrifugation for 3 times. Then 1 kg of anhydrous ethanol is used each time to perform stirring cleaning-centrifugation for 2 times to remove the residue adsorbed on the surface of the silver-coated nickel powder to obtain moist and clean silver-coated nickel powder. The powder is placed in a forced air drying oven and dried at 70°C for 6 hours to obtain about 697 g of clean spherical silver-coated nickel powder.
[0028] S6 surface modification: 2 g of pineol was evenly sprayed on 697 g of clean silver-coated nickel powder after drying, and then mixed evenly to obtain modified silver-coated nickel powder that can be used to prepare slurry. Figure 1 This is the SEM image of the prepared silver-coated nickel powder.
[0029] Referring to the above method, several silver-coated nickel powders shown in Table 1 were prepared by adjusting the amount of silver nitrate, and their resistivity, anti-oxidation resistivity and titration nickel content were measured respectively.
[0030] Table 1. Performance parameters of silver-coated nickel powder
[0031] [Preparation of glass powder] Weigh the raw materials according to the proportions in Table 2, and mix them to obtain a mixture; melt the mixture at 1250-1300°C for 1.5 hours, pour it into deionized water and quench it to obtain glass fragments; after filtering out the water from the glass fragments, place them in a 20L vertical ball mill, add 15kg of zirconia balls with a diameter of 5-10mm, add 2kg of deionized water and oleic acid, stir at a speed of 250r / min, and ball mill for 8 hours to obtain glass slurry; finally, sieve the glass slurry and dry it to obtain a glass powder with a particle size of 2-5μm.
[0032] Table 2. Raw material ratios for glass powder preparation Example
[0033] [Examples 1-6] The raw materials were weighed according to the proportions in Table 3, preliminarily mixed with a homogenizer, and then rolled with a three-roll mill to obtain a silver-coated nickel slurry.
[0034] Table 3. Raw material ratio table of Examples 1-6
[0035] The glass powders used in Examples 1-6 were all prepared by the method of the preparation example; the conductive powder used was a mixture of silver powder and silver-coated nickel powder. The specific composition of the conductive powder is shown in Table 4.
[0036] Table 4. Composition of conductive powders in Examples 1-6
[0037] In Example 4, two kinds of silver-coated nickel powders with silver contents of 50% (Preparation Example 6) and 30% (Preparation Example 2) were used, and the weight ratio of the two kinds of silver-coated nickel powders was 2.4: 1. In other embodiments, homemade or commercially available silver-coated nickel powders of other specifications can be selected as raw materials, and one kind of silver-coated nickel powder can be used alone or multiple kinds of silver-coated nickel powders can be mixed.
[0038] Comparison Example [Comparative Example 1] Comparative Example 1 is based on Example 1, with the difference that the conductive powder is pure silver powder.
[0039] [Comparative Example 2] Comparative Example 2 is a commercially available pure silver high temperature sintered crystalline silicon solar cell high temperature conductive paste from Heraeus, brand SOL3201.
[0040] [Comparative Example 3-6] Comparative Examples 3-6 are all based on Example 1, with the only difference being that the specifications of the silver-coated nickel powder in the conductive powder are different, as shown in Table 5 for details.
[0041] Table 5. Specifications of Silver-coated Nickel Powder in Comparative Example 3-5
[0042] Application examples and comparative examples [Application Examples 1-6] A high-temperature sintering crystalline silicon solar cell metallization method, respectively using the silver-coated nickel paste of Examples 1-6. The specific steps are: screen printing the aforementioned silver-coated nickel paste on the surface of the crystalline silicon solar cell, drying, sintering in air at 500-750°C, and completing the metallization of the crystalline silicon solar cell. The SEM image of the cross-section of the silver-coated nickel electrode after sintering by printing the silver-coated nickel paste in Example 2 is as follows: Figure 2A , Figure 2B shown.
[0043] [Comparative Application Examples 1-5] The difference between the comparative application example and the application example is that the slurries of the control examples 1 to 5 are respectively applied.
[0044] Performance testing The electrical performance test was performed on the high temperature fired crystalline silicon solar cells made by the metallization process of Application Examples 1-6 of the present invention and Comparative Application Examples 1-5.
[0045] [Total wet weight test of back auxiliary grid] The weight change of a single 166 silicon wafer before and after printing was detected by the difference method. Five wafers were measured and the average value was taken.
[0046] [IV test] The solar cells were characterized at 25°C ± 1.0°C using a commercially available IV tester "YP-CX5000" obtained from Yanpu Intelligence. The stroboscopic pulse light simulates sunlight, and its AM1.5 intensity on the surface of the cell is known to be 1000W / m. In order for the simulator to have this intensity, the stroboscopic pulse light flashes several times in a short period of time until it reaches a stable level monitored by the "1.0.0.0" software of the IV tester. The Yanpu IV tester uses a multi-point contact method to measure current (I) and voltage (V) to determine the IV curve of the battery. All values are automatically determined from the curve with the help of a running software package. As a reference standard, a calibrated solar cell obtained from ISE Freiburg and made of the same area size, the same wafer material and using the same front pattern was tested, and the data was compared with the certified values. At least 20 wafers processed in the same way were measured, and the data was analyzed by calculating the average of each value. The software provides values for conversion efficiency and line resistance.
[0047] [Contact resistance] All equipment and materials were balanced in an air-conditioned room at a temperature of 22 ± 1 ° C before measurement. In order to measure the contact resistance of the fired electrode on the doped front layer of the silicon solar cell, the MLR-5104 on-resistance test system was used. The device applies the 4-point measurement principle to estimate the contact resistance by the transfer length method (TLM). In order to measure the contact resistance, two strips of 1 cm wide were cut from the wafer perpendicular to the printed grid lines of the wafer. Each strip measures its exact width with an accuracy of 0.05 mm. The width of the fired secondary grid lines was measured at 3 different points on the strip using a digital microscope "VHX-970F" equipped with a wide-range zoom lens VH-Z250 from Keyence Corp. The width was measured 10 times at each point with 2-point measurements. The grid line width value is the average value of all 30 measurements. The contact resistance is calculated by the software package using the pointer number, the strip width and the distance between the printed secondary grids. The measurement current is set to 14 mA. A multi-contact measuring head suitable for contacting 11 adjacent grid lines is installed and made to contact 11 adjacent grid lines. The measurement is performed on 10 points equally spaced on each strip. After starting the measurement, the software determines the value of the contact resistance (in mohm) for each point on the strip. The average value of all 20 points is taken as the value of the contact resistance.
[0048] The test results are recorded in Table 6.
[0049] Table 6. Performance test results
[0050] From the data in the above table, it can be seen that the silver-coated nickel paste provided by the present invention has a slightly higher line resistance, basically the same contact resistance, and basically the same printed wet weight than pure silver paste for single-back printed crystalline silicon solar cells. The adjusted efficiency is 0.03% to 0.1% lower than that of pure silver paste. That is, it is feasible to replace the pure silver powder in the silver paste of crystalline silicon solar cells with densely coated high-reliability silver-coated nickel powder. When the silver-coated nickel paste of the present invention is used for metallization of crystalline silicon solar cells, secondary laser sintering is not required.
[0051] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A silver-coated nickel paste, characterized in that: It is prepared from the following raw materials in percentage by weight, Conductive powder 80-95%, Glass powder 1-6%, Organic resin 0.1-3%, Thixotropic agent 0.5-0.8%, Other additives 0-1%, Solvent residue; The conductive powder is a mixture of silver-coated nickel powder and silver powder in a weight ratio of 1:(0-50); the resistivity of the silver-coated nickel powder used is ≤96μΩ·cm, the anti-oxidation resistivity is ≤205μΩ·cm, and the titrated nickel content is ≤0.01mol / L.
2. The silver-coated nickel paste according to claim 1, characterized in that: The silver content of the silver-coated nickel powder is 5wt%-50wt%.
3. The silver-coated nickel paste according to claim 2, characterized in that: The silver-coated nickel powder is subjected to surface modification treatment, and the specific steps are as follows: The surface modifier of 5 / 10,000 to 5 / 1000 of the mass of the silver-coated nickel powder is evenly mixed with the silver-coated nickel powder to obtain the surface-modified silver-coated nickel powder.
4. The silver-coated nickel paste according to any one of claims 1 to 3, characterized in that: The organic resin is a mixture of one or more of PVB resin, rosin resin, acrylic resin, phenoxy resin and ethyl cellulose.
5. The silver-coated nickel paste according to any one of claims 1 to 3, characterized in that: The thixotropic agent is a mixture of one or more of polyamide wax, hydrogenated castor oil and polyethylene glycol.
6. The silver-coated nickel paste according to any one of claims 1 to 3, characterized in that: The other auxiliary agent is a mixture of one or more of palmitic acid, silane coupling agent, dimethyl silicone oil, oleic acid and TDO dispersant.
7. The silver-coated nickel paste according to any one of claims 1 to 3, characterized in that: The solvent is selected from one or more of tripropylene glycol butyl ether, dibutyl phthalate, terpineol, tributyl citrate, butyl carbitol, triethylene glycol butyl ether, diethylene glycol butyl ether and benzyl alcohol.
8. The method for preparing the silver-coated nickel slurry according to any one of claims 1 to 7, characterized in that: The raw materials are weighed according to the proportion, mixed evenly and then rolled to obtain the silver-coated nickel paste for metallization of crystalline silicon solar cells.
9. A method for metallizing a crystalline silicon solar cell, using the silver-coated nickel paste according to any one of claims 1 to 7.
10. A crystalline silicon solar cell metallization method according to claim 9, characterized in that: The specific steps are: screen printing silver-coated nickel paste on the surface of the crystalline silicon solar cell solar cell, drying, sintering in the air at 500-750° C., and completing the metallization of the crystalline silicon solar cell.
Citation Information
Patent Citations
Organic modified crystalline silicon solar cell anti-aging electrode paste and preparation method thereof
CN108538435A
Antioxidant resistance paste and preparation method thereof
CN116344097A
HJT low-temperature sintering conductive silver paste and preparation method thereof
CN117831835A
Low-temperature curing silver-coated nickel conductive paste and preparation method thereof
CN117976286A
Method for metalizing TOPCon solar cell by using silver-coated nickel paste and solar cell
CN118367063A
Cited By
Silver-nickel conductive paste for BC battery and preparation method of silver-nickel conductive paste
CN120164656A
Modified nickel powder and preparation method thereof, conductive silver-nickel slurry and TOPCon solar cell
CN121339425A
Seed layer slurry for TOPCon battery and preparation method and application thereof
CN121506586A
Silver-coated nickel conductive paste for photovoltaic cell and preparation method of silver-coated nickel conductive paste
CN122337733A